2015
DOI: 10.1002/2015ja021730
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous reconnection at a separator current layer: 1. Nature of the reconnection

Abstract: Magnetic separators, which lie on the boundary between four topologically distinct flux domains, are prime locations in three‐dimensional magnetic fields for reconnection, especially in the magnetosphere between the planetary and interplanetary magnetic fields and also in the solar atmosphere. Little is known about the details of separator reconnection, and so the aim of this paper, which is the first of two, is to study the properties of magnetic reconnection at a single separator. Three‐dimensional, resistiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…These flows drive slow, steady reconnection at the separator, which lasts much longer than the initial fast-reconnection stage. From Stevenson & Parnell [62], it is clear that the separator reconnection does not occur at the three-dimensional null points that lie at either end of the separator, but occurs at some position along its length. The initial seed location of the reconnection is likely to be where the separator current reaches a peak.…”
Section: (C) Energy Partitioning Due To Reconnection At Topological Fmentioning
confidence: 99%
See 1 more Smart Citation
“…These flows drive slow, steady reconnection at the separator, which lasts much longer than the initial fast-reconnection stage. From Stevenson & Parnell [62], it is clear that the separator reconnection does not occur at the three-dimensional null points that lie at either end of the separator, but occurs at some position along its length. The initial seed location of the reconnection is likely to be where the separator current reaches a peak.…”
Section: (C) Energy Partitioning Due To Reconnection At Topological Fmentioning
confidence: 99%
“…Stevenson & Parnell [62] considered a system involving a non-force-free three-dimensional MHS equilibria in which a separator current layer exists with current parallel to the separator. Only high-beta cases have been considered thus far; in all cases, the waves and flows generated by the reconnection carry just a fraction of the magnetic energy converted during the reconnection away from the reconnection site.…”
Section: (C) Energy Partitioning Due To Reconnection At Topological Fmentioning
confidence: 99%
“…Only generic separators exist for more than an instant in dynamic 3‐D magnetic fields (separators formed by the intersection of the spines, or one spine and a separatrix surface, from two distinct 3‐D nulls are nongeneric as any small perturbation in the field will destroy the intersection) and are formed by the intersection of the separatrix surfaces of a pair of 3‐D null points and so are special field lines that connect two null points (see Lau and Finn [], Parnell et al [], and Stevenson and Parnell [] for a basic discussion on 3‐D null points, separators, and separator reconnection).…”
Section: Introductionmentioning
confidence: 99%
“…In 3‐D, however, these four domains come together all the way along a line, the field line known as the separator, which crucially does not have zero magnetic field all the way along it. The local magnetic field in planes perpendicular to a separator may be either X type or O type in nature, as demonstrated both analytically and numerically by Parnell et al [] and also found in Stevenson and Parnell []. Thus, the name “X line,” which has in the past been used to refer to such a line, is inappropriate and should simply be reserved for scenarios in 2.5‐D.…”
Section: Introductionmentioning
confidence: 99%
“…with currents concentrated along a separator field line (Longcope & Cowley 1996;Heerikhuisen & Craig 2004;Pontin & Craig 2006;Parnell, Haynes & Galsgaard 2010;Stevenson & Parnell 2015). The papers of Priest &Priest (2016) provide an overview of the different reconnection regimes happening around the null point as well as a link to different works on this topic.…”
Section: Magnetic Topology Of Solar Flaresmentioning
confidence: 99%